Improving Reading Skill For Elementary Class at SD Melbourne School Binjai - Manik, Sondang; Pasaribu, Tiara; Rajagukguk, Rosdiana; A Sembiring, Rony; Pasaribu, Donna; Sinambela, Erika; Elfrida, Rotua; Gea, Pinta (Mejuajua: Jurnal Pengabdian pada Masyarakat, 2024)
Community service is one of  the obligation in higher education.  Tridharma of  Higher Education is education, research, and Community service . sometime that students of primary level is not important, but actually Community service for students of primary level is important in English because they are in critical period, its time for the to learn English or other language  (according to Eric Lennenbeg). They need to learn, and do  more practices. In reading comprehension students also learn new vocabulary, when they repeat the sentences they learn speaking. They learn English happily. Writer tried to teach reading comprehension with quiz exercise, the goal  of this  community services is to improve the competence for teachers and students specifically in reading comprehension. In learning reading comprehension students also improve their vocabulary as well as speaking.